Managing complexity in the public services - Haynes, Philip (London ; New York : Routledge, 2015)
"The application of complexity theory to management and the social sciences has been a key development in theory and practice over the last decade. This approach questions the possibility of finding universal methods of practice, and proposes a pragmatic and humanistic management style that evolves out of a reflective method. The focus is on practitioners observing patterns of similarity and being adaptable in decision-making.Bringing complexity theory into management reveals the importance of organizational culture and effective communication because people, their values and their objectives are at the heart of this method. Information technology provides a framework for complex communication and knowledge use, but it cannot replace highly developed professional negotiations and cooperation.This book argues that the complexity of the public service world limits the usefulness of classical and rational scientific management approaches such as New Public Management. Excessive marketization threatens a collaborative approach and overly rigid approaches to performance management and strategic management can be dysfunctional.Managing Complexity in the Public Services 2nd Edition advances a method of management practice that copes with the stark realities of the complex and unpredictable public policy world. It develops pragmatic management practices from action research that will be valuable to both academics and practitioners. The result is a new value-based practice for the post-crisis public service world"--
"Complexity theory has grown in importance over the last decade and its development has enabled a universal method of practice which proposes a pragmatic and humanistic management practice. The application of complexity theory highlights the importance of the development of an organizations culture and communication, it enables them to be dynamic whilst maintaining coherence and stability. It places the workers, their values and mission at the heart of the organizations practices, recognising that information technology may provide a framework for complex communication and knowledge use but cannot replace highly developed professional negotiations and cooperation. This new edition of Managing Complexity in the Public Services argues that the complexity of the public service world limits the usefulness of classical and rational scientific management approaches like the New Public Managerialism (NPM). As a result overly rigid approaches to performance management and strategic management can be highly dysfunctional in the public context. Managing Complexity in the Public Services takes further the articulation of a method of management practice that can cope with the stark realities of the complex and unpredictable public policy world. It develops a number of management practices developed in action research that will be of high use to both academics and practitioners and helps detail how complexity theory can be applied in practice The result is a new value based practice for the post crisis public service world"--
Includes bibliographical references (pages 150-158) and index.
Keywords: Public administration; Complexity (Philosophy)